Effect of montelukast added to inhaled budesonide on control of mild to moderate asthma. Issue 3 (1st March 2003) - Vaquerizo, M J; Casan, P; Castillo, J; Perpiña, M; Sanchis, J; Sobradillo, V; Valencia, A; Verea, H; Viejo, J L; Villasante, C; Gonzalez-Esteban, J; Picado, C
Abstract : Background: Proinflammatory leukotrienes, which are not completely inhibited by inhaled corticosteroids, may contribute to asthmatic problems. A 16 week multicentre, randomised, double blind, controlled study was undertaken to study the efficacy of adding oral montelukast, a leukotriene receptor antagonist, to a constant dose of inhaled budesonide. Methods: A total of 639 patients aged 18–70 years with forced expiratory volume in 1 second (FEV1 ) ≥55% predicted and a minimum predefined level of asthma symptoms during a 2 week placebo run in period were randomised to receive montelukast 10 mg (n=326) or placebo (n=313) once daily for 16 weeks. All patients received a constant dose of budesonide (400–1600 μg/day) by Turbuhaler throughout the study. Results: Mean FEV1 at baseline was 81% predicted. The median percentage of asthma exacerbation days was 35% lower (3.1% v 4.8%; p=0.03) and the median percentage of asthma free days was 56% higher (66.1% v 42.3%; p=0.001) in the montelukast group than in the placebo group. Patients receiving concomitant treatment with montelukast had significantly (p<0.05) fewer nocturnal awakenings and significantly (p<0.05) greater improvements in β agonist use and morning peak expiratory flow rate (PEFR). Conclusions: For patients with mild airway obstruction and persistent asthma symptoms despite budesonide treatment, concomitant treatment with montelukast significantly improves asthma control.